Prevalence and morphology of C‐shaped and non‐C‐shaped root canal systems in mandibular second molars. (4th July 2022) - Fenelon, T; Parashos, P
Abstract: Background: There are no cone‐beam computed tomography (CBCT)‐based data on the anatomy of mandibular second molars in an Australian population. This study investigated the prevalence and descending morphology of mandibular second molars with and without C‐shaped canals using retrospective analysis of CBCT scans. Methods: Scans from 715 patients were screened for the presence of C‐shaped canals and assessed for cross‐sectional configuration at five axial levels. Non‐C‐shaped molars were assessed for other morphological characteristics. Data were modelled against patient, tooth and CBCT scan characteristics. Results: A total of 1278 teeth from 657 patients were evaluated. The overall prevalence of C‐shaped canals was 13%. Cross‐sectional configuration of C‐shaped canals was variable, with an average of 2.8 unique cross‐sections per tooth. Non‐C‐shaped teeth were predominantly Vertucci Type II (60%) and Type IV (29%) configurations in mesial roots, and Type I (91%) in distal roots. Additional roots occurred in 4.3% of teeth and there was a significant association between radix paramolaris and distal root bifurcation ( P < 0.001). Conclusions: Cross‐sectional analysis confirmed the complexity and variability of C‐shaped canals. Clinicians should be cognizant of the prevalence and variability of C‐shaped root canal morphology and how this may affect endodontic treatment.